The guns of Navarone [videorecording (DVD)] - Thompson, J. Lee (John Lee), 1914-2002; Peck, Gregory, 1916-2003; Niven, David, 1910-1983; Quinn, Anthony, 1915-2001; Foreman, Carl; MacLean, Alistair, 1922-1987 (Columbia TriStar Home Video, 2000)
A specialized commando team is assembled to destroy the German Army's two long-range field guns at Navarone, because they control a strategic channel in the Aegean Sea and prevent the rescue of 2,000 trapped British soldiers.